Strategies for Promoting HIV Testing Uptake: Willingness to Receive Couple-based and Collective HIV Testing among a Cross-sectional Online Sample of Men Who Have Sex with Men in China - Wei, Chongyi (2014)
OBJECTIVES: Low rates of HIV testing drive the rapidly growing HIV epidemic among men who have sex with men (MSM) in China. We examined the potential utility of couple-based and collective HIV testing strategies among Chinese MSM. METHODS: A cross-sectional online survey was conducted among 1,113 MSM in 2013. Multivariable logistic regression analyses were conducted to identify factors associated with willingness to receive couple-based and collective testing. RESULTS: Acceptability of couple-based testing was very high among participants (86.1%), with a moderate level of interest in collective testing (43.2%). Being “out” to others about one's sexual identity (AOR = 1.48, 95% CI: 1.01, 2.17) and having ever had an HIV test (AOR = 3.05, 95% CI: 2.10, 4.33) were associated with willingness to receive couple-based testing. Having multiple male anal sex partners in the past three months was associated with willingness to participate in collective testing (AOR = 1.43, 95% CI: 1.03, 1.99). DISCUSSION: Couple-based and collective HIV testing could help better control the HIV epidemic among Chinese MSM if implemented and promoted in a culturally competent manner.